Spatial Frequency Thresholds for Detecting Latent Facial Signals of Threat. (March 2019) - Watier, Nicholas; DeGagne, Brock
This study examined whether latent facial signals of threat can be detected at more extreme ranges of spatial frequencies (SFs), and thus with fewer frequencies from an optimal middle band for face identification, compared with latent nonthreatening facial signals. Using an adaptive staircase procedure and a two-interval forced-choice same-different task, SF thresholds from the lower and higher ends of the SF spectrum were obtained for nonexpressive threatening and nonthreatening faces. Threatening faces were discriminated from neutral faces more quickly and accurately, and engendered more extreme SF thresholds, compared with nonthreatening faces. The results indicate that the components of latent threatening facial signals can be detected under a greater degree of impoverished visual information for face processing compared with their nonthreatening counterparts.